High perfomance centre restructuring notions around gaming - Laird, Ceri (My University, 2017)
The aim of this master thesis is to explore alternative ways in which gaming and technology can be seen, not only in Johannesburg but on a world wide scale. This comes in the form of a new school as part of Wits, interactive museum, game development centre and a facility to develop professional gamers. With Braamfontein already under massive growth in this sector and its centralized location, it is a perfect spot to facilitate this thesis. The aim is to restructure the notions people have about gaming, the industry and the future. Further positive strengthening of the ideas by the placement of the building on the site, and working with the relation to the landscape in a new technology orientated understanding of place and identity.
This document is submitted in partial fulfillment for the degree: Master of Architecture (Professional) at the School of Architecture and Planning, University of the Witwatersrand, Johannesburg, South Africa in the year 2017